2022
DOI: 10.1111/pcmr.13039
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed human pigmented skin/epidermis models achieve epidermal pigmentation through melanocore transfer

Abstract: The skin acts as a barrier to environmental insults and provides many vital functions. One of these is to shield DNA from harmful ultraviolet radiation, which is achieved by skin pigmentation arising as melanin is produced and dispersed within the epidermal layer. This is a crucial defence against DNA damage, photo‐ageing and skin cancer. The mechanisms and regulation of melanogenesis and melanin transfer involve extensive crosstalk between melanocytes and keratinocytes in the epidermis, as well as fibroblasts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The formation of melanin SPNCs within keratinocytes is a well‐known phenomenon that protects nuclear DNA from UV‐induced damage 62 . A modest number of pigmented HSEs have been reported in the literature, however they lack extensive characterization, with limited evidence provided relating to the formation of SPNCs 32,34,41,63–65 . To our knowledge, presence of SPNCs in vitro has only been reported by Gibbs et al 66 in a reconstructed epidermal system requiring patient‐derived tissue for construction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of melanin SPNCs within keratinocytes is a well‐known phenomenon that protects nuclear DNA from UV‐induced damage 62 . A modest number of pigmented HSEs have been reported in the literature, however they lack extensive characterization, with limited evidence provided relating to the formation of SPNCs 32,34,41,63–65 . To our knowledge, presence of SPNCs in vitro has only been reported by Gibbs et al 66 in a reconstructed epidermal system requiring patient‐derived tissue for construction.…”
Section: Discussionmentioning
confidence: 99%
“…62 A modest number of pigmented HSEs have been reported in the literature, however they lack extensive characterization, with limited evidence provided relating to the formation of SPNCs. 32,34,41,[63][64][65] To our knowledge, presence of SPNCs in vitro has only been reported by Gibbs et al 66 in a reconstructed epidermal system requiring patient-derived tissue for construction. Although the use of patient-derived tissue can lead to personalized medicine applications, the availability of tissue can be a limiting factor in the creation of such models, restricting their use for industrial pursuits and large scale applications.…”
Section: Desquamation Is Major Regulatory Process Involved In Melanin...mentioning
confidence: 94%
“…[19][20][21] On the other hand, Tarafder et al suggested coupled exo/endocytosis of melanocores as a major mechanism in constitutive skin pigmentation. 16,17,24 In fact, keratinocytes internalize both membrane-bound melanosomes and melanocores, 21,25 and both forms are found in the extracellular space, 16 suggesting different transfer mechanisms could co-exist in physiological and pathological circumstances. The exact mechanism how melanocytes transfer melanosomes to keratinocytes in melasma skin warrants incorporating in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that melanosomes are transferred using the melanosome‐rich package (pigment globules) in darkly pigmented skin 19–21 . On the other hand, Tarafder et al suggested coupled exo/endocytosis of melanocores as a major mechanism in constitutive skin pigmentation 16,17,24 . In fact, keratinocytes internalize both membrane‐bound melanosomes and melanocores, 21,25 and both forms are found in the extracellular space, 16 suggesting different transfer mechanisms could co‐exist in physiological and pathological circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 2h pulse, organelles with the lamellar morphology typically associated with lysosomes that also contained aggregated gold could be observed fusing with melanin-containing vesicles (Figure 2A). We then moved to Reconstructed Human Pigmented Epidermis (RHPE) as an in vitro human model system, which we previously showed to mimic the essential features of human pigmentation (Hall and Lopes-Ventura et al, 2022). We observed by TEM similar examples of melanin within compartments with lysosomal morphology (Figure 2B).…”
Section: Melanin-containing Phagosomes Fuse With Pre-existing Lysosomesmentioning
confidence: 93%